2009
DOI: 10.1007/s10803-009-0841-1
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Perception and Lateralization of Spoken Emotion by Youths with High-Functioning Forms of Autism

Abstract: The perception and the cerebral lateralization of spoken emotions were investigated in children and adolescents with high-functioning forms of autism (HFFA), and age-matched typically developing controls (TDC). A dichotic listening task using nonsense passages was used to investigate the recognition of four emotions: happiness, sadness, anger, and neutrality. The participants with HFFA did not differ significantly in overall performance from the TDC, suggesting that the pervasive difficulty in processing emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…In fact, recent evidence suggests that the often observed right-hemispheric dominance in processing facial emotional expressions may indeed depend on the right-lateralized network for face processing (Worley & Boles, 2016). In this regard, it is interesting that individuals who show developmental delays associated with autism spectrum disorder (and whose prevalence is particularly high in blind children, Jure, Pogonza, & Rapin, 2016) also present abnormal hemispheric lateralization in different tasks (Floris et al, 2016; Herringshaw, Ammons, DeRamus, & Kana, 2016; but see Baker, Montgomery, & Abramson, 2010), including atypical hemispheric specialization for faces (Keehn, Vogel-Farley, Tager-Flusberg, & Nelson, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…In fact, recent evidence suggests that the often observed right-hemispheric dominance in processing facial emotional expressions may indeed depend on the right-lateralized network for face processing (Worley & Boles, 2016). In this regard, it is interesting that individuals who show developmental delays associated with autism spectrum disorder (and whose prevalence is particularly high in blind children, Jure, Pogonza, & Rapin, 2016) also present abnormal hemispheric lateralization in different tasks (Floris et al, 2016; Herringshaw, Ammons, DeRamus, & Kana, 2016; but see Baker, Montgomery, & Abramson, 2010), including atypical hemispheric specialization for faces (Keehn, Vogel-Farley, Tager-Flusberg, & Nelson, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…At the same time, several studies have demonstrated comparable abilities in individuals with HFA and TD controls (Baker, Montgomery, & Abramson, 2010;Brennand, Schepman, & Rodway, 2011;Grossman, Bemis, Plesa Skwerer, & Tager-Flusberg, 2010;O'Connor, 2007), suggesting that the perception of emotional prosody is not significantly impaired in individuals with HFA. Although it remains unclear why research in this area has yielded such inconsistent findings, possible explanations that have been ventured include effects of task demands, influences of verbal and nonverbal IQ on emotion perception, and heterogeneity within the individuals with HFA.…”
mentioning
confidence: 90%
“…Accurate recognition of affect is a requisite skill for adaptive social functioning and a noted domain of impairment in individuals with autism spectrum disorder (ASD; Baker, Montgomery, & Abramson, 2010;Philip et al, 2010;Rump et al, 2009). Deficits in identification of emotional content in faces (Rump et al, 2009) and voices (e.g., prosody; Baker et al, 2010) are well-documented in this population and are posited to represent a core deficit (Philip et al, 2010).…”
Section: Study 1 Multimodal Emotion Processing In Autism Spectrum Dismentioning
confidence: 99%
“…Deficits in identification of emotional content in faces (Rump et al, 2009) and voices (e.g., prosody; Baker et al, 2010) are well-documented in this population and are posited to represent a core deficit (Philip et al, 2010). Nevertheless, some research reveals subgroups of individuals with ASD who exhibit relatively preserved emotion recognition ability (Bal et al, 2010;Kuusikko et al, 2009;O'Connor et al, 2005), highlighting the under-studied topic of variability within ASD.…”
Section: Study 1 Multimodal Emotion Processing In Autism Spectrum Dismentioning
confidence: 99%